2017
DOI: 10.5194/acp-17-13317-2017
|View full text |Cite
|
Sign up to set email alerts
|

The role of 1-D and 3-D radiative heating in the organization of shallow cumulus convection and the formation of cloud streets

Abstract: Abstract. The formation of shallow cumulus cloud streets was historically attributed primarily to dynamics. Here, we focus on the interaction between radiatively induced surface heterogeneities and the resulting patterns in the flow. Our results suggest that solar radiative heating has the potential to organize clouds perpendicular to the sun's incidence angle.To quantify the extent of organization, we performed a high-resolution large-eddy simulation (LES) parameter study. We varied the horizontal wind speed,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 39 publications
4
62
2
Order By: Relevance
“…AVE_SFC_RADSW also produces larger clouds and less count of clouds than the control. This is consistent with results from previous studies with more idealized setups (e.g., Gronemeier et al, ; Horn et al, ; Jakub & Mayer, ). When the shift distance increases to more than 3 km, further change in cloud size and cloud count becomes small in Figure , reminiscent of what we see in the cloud LWP response in Figure .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…AVE_SFC_RADSW also produces larger clouds and less count of clouds than the control. This is consistent with results from previous studies with more idealized setups (e.g., Gronemeier et al, ; Horn et al, ; Jakub & Mayer, ). When the shift distance increases to more than 3 km, further change in cloud size and cloud count becomes small in Figure , reminiscent of what we see in the cloud LWP response in Figure .…”
Section: Resultssupporting
confidence: 93%
“…For a 3‐km shift (which corresponds roughly to a 60° solar incidence angle for 20060808), the cloud LWP response (to removing cloud shading‐induced heterogeneities) becomes negative and larger in magnitude than the (positive) response with no shift for both 20060808 and 20070514 in d03. These results are consistent with findings from recent studies by Gronemeier et al () and Jakub and Mayer () and adds more complexity to the land‐atmosphere coupling in the presence of shallow clouds.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For instance, Jakub and Mayer (2017) show that the three-dimensional radiative effects on the surface leads to the organization of cumulus clouds streets, while a three-dimensional incanopy radiative transfer can improve modeled photosynthesis levels (Kobayashi et al, 2012). Although this also has not been accounted for in regional and global weather models, it is known to influence in-canopy processes that ultimately affect the overlying atmosphere.…”
Section: Moving Forward In Land-atmosphere Interaction Studiesmentioning
confidence: 99%
“…While many components of the Earth system interact with radiation, clouds play a key role because of their strong impact (globally cooling the Earth; Ramanathan et al, ), their high frequency of occurrence (Rossow & Dueas, ), and their inherent complexity in both space and time (Davis et al, ). Radiation and its interactions with clouds are involved in various atmospheric applications at a large range of scales: from the Earth's energy balance and cycle relevant to numerical weather predictions (Hogan et al, ) and climate studies (Cess et al, ; Dufresne & Bony, ) to the inhomogeneous heating and cooling rates that modify dynamics and cloud processes at small scales (Jakub & Mayer, ; Klinger et al, , ), and to the retrieval of atmospheric state and properties from radiative quantities such as photon path statistics, spectrally resolved radiances, and polarized reflectances (Cornet et al, ), observed by both active and passive remote sensors.…”
Section: Introductionmentioning
confidence: 99%